2019
DOI: 10.1051/0004-6361/201936013
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a giant and luminous Lyα+C IV+He II nebula at z = 3.326 with extreme emission line ratios

Abstract: We present the discovery of HLock01-LAB, a luminous and large Lyα nebula at z = 3.326. Medium-band imaging and long-slit spectroscopic observations with the Gran Telescopio Canarias reveal extended emission in the Lyα 1215Å, C iv 1550Å, and He ii 1640Å lines over ∼ 100 kpc, and a total luminosity L Lyα = (6.4±0.1)×10 44 erg s −1 . HLock01-LAB presents an elongated morphology aligned with two faint radio sources contained within the central ∼ 8 kpc of the nebula. The radio structures are consistent to be faint … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 130 publications
0
11
0
Order By: Relevance
“…We broadly expect the above findings to hold valid over the much wider area of DR1 (bigger by a factor of ∼ 500), hence to select a mixture of extremely Lyα-bright, rare star-forming galaxies (e.g., Sobral et al 2016;Hartwig et al 2016;Cai et al 2017a;Shibuya et al 2018;Cai et al 2018;Marques-Chaves et al 2019) and luminous AGN/QSOs, numerically dominated by the latter source class. Indeed, our work selects objects showing strong and reliable NB excess, without employing any further criterion to disentangle its nature.…”
Section: Agn/qsos or Star-forming Galaxiesmentioning
confidence: 73%
“…We broadly expect the above findings to hold valid over the much wider area of DR1 (bigger by a factor of ∼ 500), hence to select a mixture of extremely Lyα-bright, rare star-forming galaxies (e.g., Sobral et al 2016;Hartwig et al 2016;Cai et al 2017a;Shibuya et al 2018;Cai et al 2018;Marques-Chaves et al 2019) and luminous AGN/QSOs, numerically dominated by the latter source class. Indeed, our work selects objects showing strong and reliable NB excess, without employing any further criterion to disentangle its nature.…”
Section: Agn/qsos or Star-forming Galaxiesmentioning
confidence: 73%
“…Extended He ii emission is commonly observed within the extended Lyα emitting regions surrounding high-z radio galaxies (e.g. Maxfield et al 2002;Villar-Martín et al 2007a,b;Morais et al 2017;Marques-Chaves et al 2019). Broad line profiles and alignments with the radio-jet axes indicate that He ii is, at least in part, powered by jet-gas interactions in those objects.…”
Section: Interpretation Of Higher-order Moment Mapsmentioning
confidence: 99%
“…The distinctive observational feature of LABs with respect to similarly extended and luminous high-z Lyα nebulae around radio galaxies (e.g. Morais et al 2017;Vernet et al 2017;Marques-Chaves et al 2019), radio-loud quasars (e.g. Smith et al 2009;Roche et al 2014), or radio-quiet quasars (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies over the past 5-6 yr have revealed giant Lyα nebulae around individual high-redshift galaxies and QSOs (e.g., Martin et al 2014aMartin et al , 2014bCai et al 2018) as well as connecting pairs of QSOs (Arrigoni Battaia et al 2019b). Multiphase observations of similar nebulae have also begun to emerge (Cantalupo et al 2019;Marques-Chaves et al 2019). However, to fully characterize the morphology, composition, and dynamics of the CGM, large samples with multiwavelength observations are needed.…”
Section: Introductionmentioning
confidence: 99%